Islamic family law: conflict of jurisdict between syariah court in Malaysia / Ismail Baharom @ Abdul Rahim and Norsharizah Ismail - Baharom @ Abdul Rahim, Ismail; Ismail, Norsharizah (2005)
The fundamental of this research is to find out whether in a present conflict between husband and wife, which Islamic Marital Law shall be applicable. According to the Federal Constitution, Islamic matters are within the ambit of state jurisdiction. Each state have their own Islamic Law which may varied from states to states, therefore the question is whenever there are clashes between the state decision made by one Syariah Court in one state, and another Syariah Court in another state which one will prevail. This research shall be based on methods that will be conducted like analyzing the relevant law whether it is consistent or ambiguous by interpreting the statutes and looking at judicial decisions on cases that relates to this subject if there is any, and summarizing those cases. This study shall also establish whether the judgment of the cases is related and coherent with the local custom and cultural context. For additional to our sources of study, we will be conducting a few interviews in order to know how serious the situation would be when the decision from one Syariah Court may differ from the other. We hope to gain something from the interviews conducted mainly from the Syariah lawyers to add into the depth of this study. From the result out of this research, we hope to expend the knowledge regarding this matter although certain people may regards it as a small issue but actually it is not. Therefore we hope that the public will aware that the matters at hand are serious.